Critical Theories and the Question of Values - Harrison, Peter (Zygon, 2026)
This review of Critical Approaches to Science and Religion by Myrna Perez Sheldon, Ahmed Ragab, and Terence Keel welcomes this new collection and points to some of the ways in which it can, and has already, broaden(ed) and enrich(ed) the field. A particular focus is the editors' proposal that critical studies can bring a new normative perspective to the field - one that moves it beyond the models of conflict and complexity to offer prescriptions about shared values and how we should live. A distinction is made between the scholarly commitments typical of historians, which focus on neutrality and objectivity, and those in the fields of critical studies, which tend more towards advocacy. Questions are raised about the grounds of our normative commitments, especially in a post-liberal context, and the role they should play in our scholarship.